Pengembangan Intervensi Manajemen Hemodialisa Untuk Mengatasi Hipervolemia pada Pasien Chronic Kidney Disease (CKD) - Idramsyah, Idramsyah; Adhi Nugraha, Bayu (Madago Nursing Journal, 2023)
Background: Hypervolemia can occur in patients with chronic kidney diseases. Hemodialysis management consists of various nursing activities aimed at maintaining fluid balance. This descriptive case study aims to provide an overview of the application of hemodialysis management to treat hypervolemia in chronic kidney disease patients. Methods: This qualitative research uses a descriptive case study design with a nursing care process approach. There were 2 participants, namely end-stage CKD patients who experienced hypervolemia and met the indications for hemodialysis. Results: The development of nursing activities in hemodialysis management begins with a focus on assessment of nutritional and fluid needs in the nursing diagnosis of hypervolemia, with fluid balance outcome standards. Edema decreased, blood pressure was normal, and body weight decreased. Conclusion: Hemodialysis management can be applied to optimize fluid balance in CKD patients.